Bank good will, build relationships for effective policing. Issue 3 (July 2015) - Hope, Joan
<x xml:space="preserve">Abstract</x> The mission of Francis Mackesy's unit is to provide an environment where students can learn while having the flexibility to grow into adults. He's director of public safety and chief of the police department at the University of North Florida.